RANCANG BANGUN APLIKASI PENGELOLAAN PEMESANAN BERBASIS WEB MENGGUNAKAN PHP DAN BOOTSRAP PADA KAFE KEBON DJATI CIOMAS - Alfaiz, Muhammad; Suhendra Anjar Dinata; Yose Eduar Muda (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
Technological developments in recent decades have changed the way people interact and socialize, including in Indonesia. The younger generation, especially millennials and Gen Z, tend to seek out gathering places such as cafes that offer comfort, modern facilities, and an aesthetic atmosphere. One cafe that follows this trend is Kafe Kebon Djati in Ciomas, Bogor. However, as the number of visitors increases, this cafe faces the problem of long queues that impact customer satisfaction and employee performance. This study aims to determine the ordering and payment methods at Kafe Kebon Djati, develop a web-based ordering management application using PHP 7 and Bootstrap 3, and assess the application's effectiveness in addressing queue problems. The research method used is Research and Development (R&D), with the steps of designing, developing, and testing the ordering application. The results of this study are expected to provide an effective solution to speed up the service process, reduce ordering errors, and increase customer satisfaction. By implementing a web-based ordering system, Kafe Kebon Djati can manage high visitor volumes more efficiently, especially during peak hours.